2021
DOI: 10.1016/j.bja.2021.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of measuring postoperative cognitive dysfunction: a systematic review

Abstract: Background: Postoperative cognitive dysfunction (POCD) is an adverse outcome that impacts patients' quality of life. Its diagnosis relies on formal cognitive testing performed before and after surgery. The substantial heterogeneity in methodology limits comparability and meta-analysis of studies. This systematic review critically appraises the methodology of studies on POCD published since the 1995 Consensus Statement and aims to provide guidance to future authors by providing recommendations that may improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 27 publications
(29 reference statements)
0
49
1
Order By: Relevance
“…Post-operative delirium (POD) is characterized by agitation or apathy and affects around 19–28% of patients during the days after surgery ( Ho et al 2021 ); post-operative cognitive dysfunction (POCD) describes a decline in cognitive test performance across surgery that can last weeks to years. At 3 to 6 months, POCD can be detected in around 10–25% of patients ( Borchers et al 2021 ). This article aims to provide a narrative review of the currently limited evidence on the cognitive epidemiology of post-operative cognitive impairment.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 99%
“…Post-operative delirium (POD) is characterized by agitation or apathy and affects around 19–28% of patients during the days after surgery ( Ho et al 2021 ); post-operative cognitive dysfunction (POCD) describes a decline in cognitive test performance across surgery that can last weeks to years. At 3 to 6 months, POCD can be detected in around 10–25% of patients ( Borchers et al 2021 ). This article aims to provide a narrative review of the currently limited evidence on the cognitive epidemiology of post-operative cognitive impairment.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 99%
“…Finally, the negative finding may have resulted from the relatively short intervals between the baseline examination and the postoperative examination of the MMSE-K and cognitive battery of tests. The POCD test is usually performed within seven days or before/at discharge from the hospital to abate the acute effects of hospitalization, anesthesia, and surgery [ 28 ]. However, in a previous study by Silbert et al, the authors reported that 30% of patients had neuropsychological changes within 18 h after cardiac surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PNDs, especially POCD, is complex requiring neuropsychological tests which are varied in studies. A recent systematic review noted that in 274 existing studies of POCD, diagnosis was based on 259 different cognitive assessment tools (Borchers et al, 2021). Moreover, neuropsychological tests have been undertaken at variable time intervals after anesthesia and surgery.…”
Section: Discussionmentioning
confidence: 99%